Effects of Cooperative and Self-Learning Strategies on Physical Education and Sport Class - عطا الله, أحمد; بن خالد, الحاج; تواتي, حياة (International Journal for Cross-Disciplinary Subjects in Education (IJCDSE), 2015)
Th is study aims to determine the effect of using some Learning Strategies for the implementing of Competency -Based Approach in the physical and sport education class. It is an attempt to identify the effects of using each Learning Strategy through the improvement of psychomotor skills relating to the chosen sport activities. The experiment protocol of three homogeneous groups (two experimental groups and one control) was used in this study, based on pre and post measurements. The test sample consisted of (72 students) of second year at high school, and it is divided in three groups, i.e. each group is composed of 24 students (12 males, 12 females). This study is based on skill tests for measuring psychomotor capacity of students, to whom the educational program has been applied. The first experimental group is exposed to Cooperative Learning Strategy; the second experimental group is subjected to Self- Learning strategy and the control group to the traditional method. Based on the obtained results, we have concluded that the usage of Cooperative Leaning Strategy is the most appropriate strategy for achieving the implementation of the Competency- Based Approach in the physical and sport education class.
Keywords: Effects of Cooperative and Self-Learning Strategies on Physical Education and Sport Class